If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying I + -1y = (-10) I + -1y = -10 Solving I + -1y = -10 Solving for variable 'I'. Move all terms containing I to the left, all other terms to the right. Add 'y' to each side of the equation. I + -1y + y = -10 + y Combine like terms: -1y + y = 0 I + 0 = -10 + y I = -10 + y Simplifying I = -10 + y
| -4x+4(4x-6)=4(6x+4)-4 | | 26x+12y=0 | | (4x+13)=log[3](9x-2) | | -8/10c=7/10 | | 2.3=(v/1.2) | | (3x-9)/(4x-16) | | 10.261/3. | | 7m^2=-27m-18 | | cy^2+by+a=0 | | 3x^2-31x+36= | | 7v^2+44v=-12 | | 51=4x^2-13 | | p/-6=-7 | | ab-12c=3forc | | 2cos(x)+3=2 | | 5p^2=-2p | | xy+6z=9forx | | 7/9d=11 | | y=((2b^3)c)(5ab^2) | | x^2+4x-729=0 | | 12+4m=3 | | 3x-9=(-19) | | r^2*2r=0 | | 15+6b+6b=4b-1-6b | | 2+0.6*x=2 | | 0=-192+x^2+4x | | 7n^2=-35+54n | | 4(x-5+2)=44 | | 192=x^2+4x | | 1/7/2/3 | | 7m^2-12=-17m | | 9(x+9)=10 |